A Produksi parselai (selai Parijoto) sebagai upaya pemanfaatan tanaman lokal melalui pemberdayaan ekonomi kreatif kelompok Aisyiyah Bakalan Krpayak Kudus : Indonesia - Mundriyastutik, Yayuk; Purbowati, Purbowati; Mustaqim, Yunus; Solikhati, Anisa; Bertama, Evyan Vanessha Sashum; Wibowo, Arbi Suryo; Saputro, Wahyu Aditya (UII, 2025)
Parijoto jam is an innovative food product that comes from parijoto fruit, a typical fruit of Kudus City. Mothers who are members of the Aisyiyah Branch of Bakalan Krapyak Kudus Village have entrepreneurial potential in the field of food products. The aim of the service is to improve partners' skills in making parijoto jam (parsley) and marketing it as a typical Kudus food preparation. The process of making this jam uses heating and sugaring methods, sugaring is what makes the jam product have a longer shelf life. The parijoto jam product produced has a sweet, sour taste and has a thick texture according to jam standards and has a shelf life of 2 months at room temperature. The training activity was carried out for two days, the first day was socialization about the benefits and methods of processing parijoto fruit, followed by demonstrations and joint practice in making parsley. On the second day, training was held on how to market products, apply for production permits and halal certificates. A total of 30 participants took part in the activity. Evaluate activities with methods pre and post-test, and by asking participants questions about the material. The result was an increase in participants' knowledge after being given socialization and training, namely the average score pre-test 29 increased to 42 after training. Some participants were also able to answer questions correctly. Furthermore, it is necessary to provide assistance in the implementation of production and business sustainability by participants.